The change of productivity and quality of spring barley grain with the improvement of the varieties’ adaptability - O. A. Yusova; P. N. Nikolaev (Зерновое хозяйство России, 2021)
The purpose of the current study was to determine the correlation between adaptability parameters of the spring barley varieties and grain productivity and the main indicators of its quality. The study was conducted from 2011 to 2019 in the conditions of the southern forest-steppe of Western Siberia. The protein percentage in grain, raw oil, starch and husk content of grain were determined according to the Pleshkov and Berkutova methods. The mathematical processing was carried out according to the methodology of Dospekhov, Eberhard and Russell. According to the trial, low productivity of spring barley was recorded in 2012, 2013 and 2016 (2.36–2.92 t/ha) with low values of the index of environmental conditions (-1.32; -1.88). Higher productivity was recorded in 2011, 2015, 2018 and 2019 (5.26-5.89 t/ha), with high values of the index of environmental conditions (1.02–1.65). The productivity of the standard variety ‘Omskiy 95’ varied from 2.11 t/ha (in 2016) to 5.91 t/ha (in 2015). The varieties ‘Sibirskiy Avangard’, ‘Sasha’, ‘Omskiy 100’ exceeded the standard variety (+0.47; +1.97 t/ha to standard). An increased content of raw oil in grain was recorded in the varieties ‘Omskiy 9’1 and ‘Sasha’ (0.4-0.6% to standard). The varieties ‘Omskiy 91’, ‘Sibirskiy Avangard’, ‘Omskiy 90’, ‘Omskiy 96’ and ‘Omskiy 100’ were characterized by a reduced husk content of grain (-0.7; -1.4% to standard). The barley varieties ‘Sibirskiy Avangard’ and ‘Sasha’ (bi > 1; σ2 d < 1) were highly responsive and stable to improving environmental conditions. The improvement of adaptability (bi) of barley varieties did not have a significant effect on grain productivity and quality (r = 0.109±0.020 and 0.232±0.035). The stability (σ2 d) of the varieties was characterized by an average direct correlation with starch content in grain (r = 0.429±0.120), a strong direct correlation with oil content in grain (r = 0.656±0.105). There was identified an average inverse correlation between stability (σ2 d) and protein and husk content in grain (r = -0.399±0.060 and -0.447±0.055). There was a weak correlation with productivity (r = -0.204±0.040).